Geographic access to lung cancer screening among eligible adults living in rural and urban environments in the United States. Issue 8 (15th February 2022) - Sahar, Liora; Douangchai Wills, Vanhvilai L.; Liu, Ka Kit (Antonio); Fedewa, Stacey A.; Rosenthal, Lauren; Kazerooni, Ella A.; Dyer, Debra S.; Smith, Robert A.
Abstract : Background: Although recommended lung cancer screening with low‐dose computed tomography scanning (LDCT) reduces mortality among high‐risk adults, annual screening rates remain low. This study complements a previous nationwide assessment of access to lung cancer screening within 40 miles by evaluating differences in accessibility across rural and urban settings for the population aged 50 to 80 years and a subset eligible population based on the 2021 US Preventive Services Task Force LDCT lung screening recommendations. Methods: Distances from population centers to screening facilities (American College of Radiology Lung Cancer Screening Registry) were calculated, and the number of individuals who had access within graduating distances, including 10, 20, 40, 50, and 100 miles, were estimated. Census tract results were aggregated to counties, and both geographies were classified with rural‐urban schemas. Results: Approximately 5% of the eligible population did not have access to lung cancer screening facilities within 40 miles; however, different patterns of accessibility were observed at different distances, between regions, and across rural‐urban environments. Across all distances and geographies, there was a larger percentage of the population in rural geographies with no access. Although the rural population represented approximately 8% of the eligible population, the larger percentage of the rural population with no access was noteworthy and translated into a larger number of individuals with no access at longer distance thresholds (≥40 miles). Conclusions: Disparities in access should be examined as both percentages of the population and numbers of individuals with no access in order to tailor interventions to communities and increase access. Geospatial analysis at the census tract level is recommended to help to identify optimal focus areas and reach the most people. Lay Summary: As annual lung cancer screening rates remain low, this study examines access to lung cancer screening nationwide and across rural and urban settings. A geographic information system network analysis of census tract–level populations is used to estimate access at different distances, including 10, 20, 40, 50, and 100 miles, and the results are aggregated to counties. Approximately 5% of the eligible population does not have access to screening facilities within 40 miles; however, different patterns of accessibility are observed at different distances, between regions, and across rural‐urban environments. Across all distances and geographies, there is a larger percentage of the population in rural geographies with no access. Abstract : This study uses geospatial analysis to examine access to lung cancer screening at graduating distances nationwide and across rural‐urban settings. Approximately 5% of the eligible population does not have access to lung cancer screening facilities within 40 miles; however, different patterns of accessibility are observed at different distances, between regions, and across rural‐urban environments.